Macroglobulin complement-related encodes a protein required for septate junction organization and paracellular barrier function in Drosophila. - Hall, S.; Bone, C.; Oshima, K.; Zhang, L.; McGraw, M.; Lucas, B.; Fehon, R.G.; Ward, R.E. (Development, 2014)
Polarized epithelia play crucial roles as barriers to the outside environment and enable the formation of specialized compartments for organs to carry out essential functions. Barrier functions are mediated by cellular junctions that line the lateral plasma membrane between cells, principally tight junctions in vertebrates and septate junctions (SJs) in invertebrates. Over the last two decades, more than 20 genes have been identified that function in SJ biogenesis in Drosophila, including those that encode core structural components of the junction such as Neurexin IV, Coracle and several claudins, as well as proteins that facilitate the trafficking of SJ proteins during their assembly. Here we demonstrate that Macroglobulin complement-related (Mcr), a gene previously implicated in innate immunity, plays an essential role during embryonic development in SJ organization and function. We show that Mcr colocalizes with other SJ proteins in mature ectodermally derived epithelial cells, that it shows interdependence with other SJ proteins for SJ localization, and that Mcr mutant epithelia fail to form an effective paracellular barrier. Tissue-specific RNA interference further demonstrates that Mcr is required cell-autonomously for SJ organization. Finally, we show a unique interdependence between Mcr and Nrg for SJ localization that provides new insights into the organization of the SJ. Together, these studies demonstrate that Mcr is a core component of epithelial SJs and also highlight an interesting relationship between innate immunity and epithelial barrier functions.